Does service recovery matter? Relationships among perceived recovery justice, recovery satisfaction and customer affection and repurchase intentions: the moderating role of gender - Ali, M.A. (Emerald Group Holdings Ltd., 2022)
Purpose: The purpose of this study/paper is first to determine the impact of perceived recovery justice (PRJ) (as a second-order construct) on recovery satisfaction and repurchase intentions; secondly, to investigate the mediating impact of customer affection and recovery satisfaction (on the relationship between PRJ and repurchase intentions and satisfaction and repurchase intentions, respectively); and thirdly, to examine the moderating effect of gender on the relationships between PRJârecovery satisfactionârepurchase intentions. Design/methodology/approach: The authors used a self-administrated survey technique for data collection. Afterwards, partial least square structural equation modelling was used to evaluate the data from 300 respondents (the automotive insurance industry in Punjab, Pakistan). Findings: The findings show that PRJ, recovery satisfaction and customer affection positively predict repurchase intentions. PRJ also indirectly predicts repurchase intentions through the mediating effect of recovery satisfaction. Gender has a contingent effect on the PRJâcustomer satisfactionârepurchase intentions relationship, such that the effect is higher for females than males. These findings have important theoretical and practical implications. To counter service failure, this study helps to draft effective strategies and policies for the insurance industry to make customers loyal patrons. Practical implications: These findings have important theoretical and practical implications. To counter service failure, this study helps to draft effective strategies and policies for the insurance industry to make customers loyal patrons. Originality/value: This study also tested a novel relationship, in that the authors used customer affection as a mediating factor between the satisfaction and repurchase intentions relationship. Moreover, the authors also tested the moderating role of gender in PRJârecovery satisfactionârepurchase intentions associations. Â© 2022, Emerald Publishing Limited.